Hubungan Self-Efficacy dengan Perencanaan Karier Siswa SMA - Adinda Aisya Ferari; Nurfarhanah Nurfarhanah; Rahmi Dwi Febriani; Miftahul Fikri (Journal of Society Counseling, 2026)
Career planning is an individual's ability to understand oneself, understand career-related information, and plan future goals to achieve the desired career outcomes. One factor associated with career planning is self-efficacy, which refers to an individual's belief in their ability to organize and perform actions required to achieve specific goals. This study aimed to determine the relationship between self-efficacy and career planning among students at SMA Negeri 2 Padang. This research employed a quantitative correlational approach. The population consisted of 388 eleventh-grade students, and 197 students were selected as the sample using proportional random sampling. Data were collected using self-efficacy and career planning questionnaires based on the theories of Bandura and Winkel & Hastuti. Data were analyzed using descriptive statistics and the Spearman Rank correlation test. The findings revealed that students' career planning was in the high category (74.3%) and self-efficacy was also in the high category (72.6%). The Spearman Rank correlation analysis showed a correlation coefficient of 0.739 with a significance value of p < 0.001. These results indicate a positive and significant relationship between self-efficacy and career planning. The higher the students' self-efficacy, the better their career planning.